Thermodynamic analysis of mechanical booster pump-assisted sorption thermochemical heat transformer driven by low-grade heat for building applications - Zeng, Tao; Kobayashi, Noriyuki; Wu, Jiatao; Li, Jun; Deng, Lisheng; Yang, Xiaohu; Huang, Hongyu (Frontiers in Energy Research, 2023)
Thermochemical heat transformers (THT) can offer the potential for efficient energy storage and upgrade based on a reversible solid-gas reaction. A mechanical booster pump (MBP)-assisted water-based sorption thermochemical heat transformer driven by low-grade solar thermal energy is proposed to handle variations in the heat demand of buildings. The MBP operates during the discharging process to adjust the magnitudes of temperature lift by compression ratio depending on the user’s demands. The performances of the proposed cycle employing three different reactive salts are investigated and compared with the conventional THT cycle under various operating conditions. Results indicate that compared to the conventional THT cycle, the proposed cycle achieves a maximum temperature lift of 15–17°C, 17–19°C, and 23–26°C for SrBr2, LiOH, and CaCl2 in the evaporating temperature range of 20–40°C, respectively. In the same operating conditions, SrBr2 demonstrates the highest energy and exergy efficiencies, while CaCl2 is inferior to the others due to its greater sensible heat consumption and lower reaction heat under the studied conditions. A suggestion is put forth for enhancing the temperature lift by employing a two-stage MBP-assisted cycle that utilizes the reactive salt SrBr2. Compared to the single-stage MBP-assisted cycle, the heat output temperature can be further increased by up to 3–16°C at the expense of a maximum decrease of 6.6%, 84.4%, and 9.0% in coefficient of performance (COP) based on total energy input, COP based on electricity input, and exergy efficiency, respectively, at 30°C evaporating temperature. The economic and environmental analysis indicates that the proposed system is economically and environmentally feasible and could be a promising alternative to residential water heaters.